Knowledge, attitude and practice on antimicrobial use and antimicrobial resistance among competent persons in the community pharmacies in Bhutan - Tenzin, Jigme; Tshomo, Kinley Penjor; Wangda, Sonam; Gyeltshen, Wangdi; Tshering, Gyem (Frontiers in Public Health, 2023)
Since their discovery, antimicrobials have been used to treat a variety of infections in both humans and animals caused by microbes. However, with increasing use of antimicrobials, microbes are developing resistance to the antimicrobials and many antimicrobials are becoming ineffective against certain microbes. Many factors are reported to contribute to the resistance of microbes to antimicrobials. One contributing factor is the misuse and overuse of antibiotics, occurring primarily due to the lack of knowledge, careless attitudes, and incorrect practices around the use of antibiotics. This cross-sectional survey was conducted among qualified and experienced individuals approved to undertake sale and dispensing of medicinal products in community pharmacies in Bhutan (competent persons), with the aim to assess their knowledge, attitude and practice (KAP) on antimicrobial use (AMU) and antimicrobial resistance (AMR). Results from the survey revealed that the competent persons had a good level of knowledge about antimicrobial use and antimicrobial resistance. They also had favourable attitudes towards antimicrobial resistance and rational use of antimicrobials. Their knowledge and attitude led to good practices while dispensing antimicrobials in their pharmacies. However, almost all of them had never had any opportunity to take part in activities related to antimicrobial use and antimicrobial resistance organized by the public sector. Many of them did not know about the existence of policies on use of antimicrobials or on curbing antimicrobial resistance in the country. Involvement of community pharmacies through trainings and participation in policy-making processes is seen as a vital mechanism that can eventually help achieve the goals in the national drive towards reducing antimicrobial resistance.